2016
DOI: 10.1021/acschembio.6b00056
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Up the Pieces of the Desferrioxamine B Jigsaw Defines the Biosynthetic Sequence Catalyzed by DesD

Abstract: Late-stage assembly of the trimeric linear siderophore desferrioxamine B (DFOB) native to Streptomyces pilosus involves two DesD-catalyzed condensation reactions between one N-acetyl-N-hydroxy-1,5-diaminopentane (AHDP) unit and two N-succinyl-N-hydroxy-1,5-diaminopentane (SHDP) units. AHDP and SHDP are products of DesBC-catalyzed reactions of the native diamine substrate 1,5-diaminopentane (DP). The sequence of DesD-catalyzed DFOB biosynthesis was delineated by analyzing the distribution of DFOB analogues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 41 publications
14
60
0
Order By: Relevance
“…This is in accordance with recent results from the Codd group, who established that the biosynthesis of endcapped desferrioxamine Bp roceeds via activation of the monomeric substrate HS [5]A and not via activation of the dimeric precursor pre[5+ +5]. [16] Since AvbD only produces [5+ +ab] but not [5+ +5+ +ab],i tc an be concluded that the Cs ite of AvbD in contrast to DesDi su nable to bind [5+ +ab].B ased on these results, we propose that the Cs ite of AvbD is more restrictivei n substrate acceptance than that of DesDa nd thus may only accept monomeric substrates. This difference between the C sites of DesD and AvbD may determine the number of oligomerization steps for each enzyme.…”
Section: Substrate Affinity To the Cs Ite Directs Oligomerization Stepssupporting
confidence: 91%
See 2 more Smart Citations
“…This is in accordance with recent results from the Codd group, who established that the biosynthesis of endcapped desferrioxamine Bp roceeds via activation of the monomeric substrate HS [5]A and not via activation of the dimeric precursor pre[5+ +5]. [16] Since AvbD only produces [5+ +ab] but not [5+ +5+ +ab],i tc an be concluded that the Cs ite of AvbD in contrast to DesDi su nable to bind [5+ +ab].B ased on these results, we propose that the Cs ite of AvbD is more restrictivei n substrate acceptance than that of DesDa nd thus may only accept monomeric substrates. This difference between the C sites of DesD and AvbD may determine the number of oligomerization steps for each enzyme.…”
Section: Substrate Affinity To the Cs Ite Directs Oligomerization Stepssupporting
confidence: 91%
“…Thisi si nl ine with resultsf rom the Codd group who reportedi ncorporation of an unsaturated HS [4]A precursor into desferrioxamine B. [16] Since both AvbD and DesD accept non-natural substrates, we reasoned that this promiscuity for synthetic substrates may provideameans to dissect and investigate the mechanism of type CN IS synthetases in greater detail.…”
Section: Desd Exhibits Relaxed Substrate Specificitysupporting
confidence: 67%
See 1 more Smart Citation
“…In the first step, DesA catalyzes the decarboxylation of l ‐lysine to produce 1,5‐diaminopentane (DP) for downstream processing by DesBCD. Subsequent steps involve mono‐ N ‐hydroxylation of DP to produce N ‐hydroxy‐DP (HDP; DesB), acetylation or succinylation of the N ‐hydroxy group of HDP to produce N ‐acetyl‐ N ‐hydroxy‐DP (AHDP) or N ‐succinyl‐ N ‐hydroxy‐DP (SHDP), respectively (DesC), and assembly of an AHDP‐SHDP heterodimer (DesD, round 1) with the condensation of a final SHDP unit to AHDP‐SHDP to form trimeric 1 (DesD, round 2) . The exogenous supply of diamine substrates to S. pilosus culture medium bypasses DesA and requires only functional DesBCD.…”
Section: Introductionmentioning
confidence: 99%
“…DP is the major native diamine substrate used in the biosynthesis of 1 and of other DFO‐type siderophores. 1,4‐Diaminobutane (DB), produced through the decarboxylation of l ‐ornithine, is a minor native diamine substrate used solely or in combination with DP to assemble DFOA‐type siderophores (Schemes and B) …”
Section: Introductionmentioning
confidence: 99%